Vibrant Communitites with a Postive Future Kansas PRIDE Impact 2015 - 2016 - Menon, Jaime (My University, 2016)
Summary of the 2015-2016 actiivities of the Kansas PRIDE program and affiliated communities.
Keywords: Administrative and Research Reports; Community Development